Evaluasi Dampak Implementasi MBKM Terhadap Proses Belajar Mengajar di Universitas PGRI Kanjuruhan Malang - Pieter Sahertian; Choirul Huda; Henny Leondro; Enike Dwi Kusumawati; Maris Kurniawati; Arief Rahman Hakim; Dyah Triwahyuningtyas; Romia Hari Susanti (Jurnal Bidang Pendidikan Dasar, 2022)
The purpose of this research is to evaluate the implementation of MBKM in the learning process using the case method and team based project implemented by the study program at Unikama. This research is a descriptive research with qualitative and quantitative approaches. The research method used is a survey method using a questionnaire. The research subjects were determined based on the research objectives, namely the entire academic community and stakeholders in the Unikama environment. The results of this study indicate that the implementation of the case method and Team Based Project is one method that is in accordance with the MBKM program and is actually able to provide opportunities to improve student skills, namely Creativity Skills, Critical Thinking Skills, Communication Skills, and Collaboration Skills (4C), so that better quality of graduates. The implementation of MBKM using Case Method and Team Base Project Learning has been carried out by lecturers